A multifactorial analysis of acceptance of evolution - (:unkn) unknown (My University, 2017)
Background: Despite decades of education reform efforts, the percent of the general US population accepting biological evolution as the explanation for the diversity of life has remained relatively unchanged over the past 35 years. Previous work has shown the importance of both educational and non-educational (sociodemographic and psychological) factors on acceptance of evolution, but has often looked at such factors in isolation. Our study is among the first attempts to model quantitatively how the unique influences of evolutionary content knowledge, religiosity, epistemological sophistication, and an understanding of the nature of science collectively predict an individual’s acceptance or rejection of evolution. Results: Our study population had a high acceptance of evolution, with an average score of 77.17 (95% C.I. ± 1.483) on the Measure of Acceptance of the Theory of Evolution (MATE) instrument. Our combined general linear model showed that, of the variables in our model, an understanding of the nature of science explained the greatest amount of variation in acceptance of evolution. This was followed in amount of variance explained by a measure of religiosity, openness to experience, religious denomination, number of biology courses previously taken, and knowledge of evolutionary biology terms. Conclusions: Understanding of the nature of science was the single most important factor associated with acceptance of evolution in our study and explained at least four times more variation than measures of evolutionary knowledge. This suggests that educational efforts to impact evolutionary acceptance should focus on increasing an understanding of the nature of science (which may be expected to have additional benefits towards generalized science denial). Additionally, our measure of epistemological sophistication had a unique, significant impact on acceptance of evolution. Both epistemological sophistication and an understanding of the nature of science are factors that might change throughout a liberal arts education, independent of the effect of direct evolutionary instruction.
Keywords: Acceptance of evolution; Nature of science; Epistemological sophistication; Religiosity; Knowledge of evolution; General linear model